2021
DOI: 10.1136/bmjopen-2020-045888
|View full text |Cite
|
Sign up to set email alerts
|

Economic evaluation of different routes of surgery for the management of endometrial cancer: a retrospective cohort study

Abstract: ObjectivesThe benefits of minimally invasive surgery (MIS) for endometrial carcinoma (EC) are well established although the financial impact of robotic-assisted hysterectomy (RH) compared with laparoscopic hysterectomy (LH) is disputed.DesignRetrospective cohort study.SettingEnglish National Health Service hospitals 2011–2017/2018.Participants35 304 women having a hysterectomy for EC identified from Hospital Episode Statistics.Primary and secondary outcome measuresThe primary outcome was the association betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…As they conducted a matched case control study, Sarlos et al 43 do not present adjusted costs. However, we argue that there are potential limitations in the matching used as no consideration is given to patient comorbidities, which have been identified as drivers of cost 44…”
Section: Discussionmentioning
confidence: 99%
“…As they conducted a matched case control study, Sarlos et al 43 do not present adjusted costs. However, we argue that there are potential limitations in the matching used as no consideration is given to patient comorbidities, which have been identified as drivers of cost 44…”
Section: Discussionmentioning
confidence: 99%
“…Studies demonstrate higher volume centres have lower readmission rates after MIS [ 27 , 31 ], with decreased costs [ 35 ]. NHS Scotland has invested £20 million to acquire 10 surgical robots nationally [ 36 ] and the Welsh Government has provided £4.2 million in funding (alongside £13.35 million from health boards) to create an ‘All-Wales Robotic Assisted Surgery Network’ [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are several limitations of this analysis. The preoperative clinical condition of the patient is not accounted for, and indeed in other specialties, such as gynaecology, it has been suggested that the higher cost of a robotic approach is influenced by the fact that patients undergoing robotic surgery tend to be more comorbid than patients undergoing laparoscopic surgery, and not just by the surgical approach alone [ 21 ]. Furthermore longer-term clinical and economic outcomes were not evaluated.…”
Section: Discussionmentioning
confidence: 99%